2012
DOI: 10.1530/eje-11-0783
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in circulating fibroblast growth factor 21 after an oral fat load is related to postprandial triglyceride-rich lipoproteins and liver fat

Abstract: Background: Elevated levels of circulating fibroblast growth factor 21 (FGF21) are commonly encountered in type 2 diabetes, dyslipidemia, and non-alcoholic fatty liver disease, all of which share exaggerated postprandial lipemia as a common proatherogenic feature. How FGF21 responds to an oral fat load in man is unknown. Methods: We measured liver fat contents and subcutaneous and visceral fat volumes in 47 healthy subjects, who also underwent an oral fat load with measurements of plasma FGF21 and free fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
3
27
1
1
Order By: Relevance
“…After administration of poloxamer 407, we observed a signifi cant decrease in VLDL-TG secretion in plasma in PSA-and PSE-fed mice Hepatic triglyceride levels have been described to determine for the number and size of VLDL-TG particles (28)(29)(30). However, in our study, hepatic triglyceride concentrations did not differ between the HFD-and PSE/ was examined ( 36 ).…”
Section: Discussioncontrasting
confidence: 47%
“…After administration of poloxamer 407, we observed a signifi cant decrease in VLDL-TG secretion in plasma in PSA-and PSE-fed mice Hepatic triglyceride levels have been described to determine for the number and size of VLDL-TG particles (28)(29)(30). However, in our study, hepatic triglyceride concentrations did not differ between the HFD-and PSE/ was examined ( 36 ).…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, one study reported on a decrease in postprandial FGF-21 concentration after oral fat load in healthy subjects and postulated that it was modulated by postprandial accumulation of triglyceride-rich lipoprotein fractions [17]. Another study examined changes in FGF-21 concentration, glucose, insulin and C-peptide levels after 75-g oral glucose tolerance test in healthy subjects, people with impaired glucose tolerance and patients with T2DM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations and hepatic FGF21 mRNA expression increase during fasting and starvation, whereas in the fed state FGF-21 expression and plasma levels are low in rodents as well as in healthy human subjects [20,21]. The main stimuli that induce hepatic FGF-21 expression during fasting are free fatty acids (FFAs).…”
Section: In Vitro and Animal Studiesmentioning
confidence: 99%
“…Ingestion of a mixed meal consisting of fat, carbohydrates, and protein suppresses FGF-21 concentrations 4-h postprandially in metabolically healthy subjects [21]. After an oral glucose tolerance test, the FGF-21 nadir is reached after 60 min and the fasting values, as well as the post-glucose decline, correlates inversely with glucose and insulin levels [64].…”
Section: Fgf-21 and Human Metabolismmentioning
confidence: 99%
See 1 more Smart Citation